Complete your dissertation or thesis in two semesters or less - Ogden, Evelyn Hunt (Distributed by National Book Network, 2007)
This newly updated guide describes how to effectively and efficiently manage the dissertation or thesis process in two semesters or less. Written for doctoral and master's degree students enrolled in on-campus programs and students pursuing accelerated and online-based degree programs, this book demystifies the seemingly daunting process. From choosing a topic and advisor, to efficient researching and the actual writing and defense, Complete Your Dissertation or Thesis in Two Semesters or Less provides students with all the information needed to conquer this academic experience. Updates to this edition include an update to the length of graduate studies and the technological advantages now available to graduate students. - Publisher. A dissertation or thesis need not be a lengthy, tedious process; but a relatively short, tolerable, and most importantly, rewarding experience. Written for doctoral and master's degree students, this book aims to demystify this process, describing how to effectively and efficiently complete a dissertation or thesis in two semesters or less.